Ant type specimens (Hymenoptera, Formicidae) in the collection of Volodymyr Opanasovych Karawajew. Communication 1. Dorylinae, Poneromorpha and Pseudomyrmecinae - Radchenko, Alexander G.; Fisher, Brian L.; Esteves, Flavia A.; Martynova, Ekateryna V.; Bazhenova, Tatyana N.; Lasarenko, Svetlana N. (Zootaxa, 2023)
The collection of Volodymyr Opanasovych Karawajew, stored at the Schmalhausen Institute of Zoology of the National Academy of Sciences of Ukraine (SIZK, Kiev), is one of the richest ant collections of the world. It contains more than 20,000 dry mounted specimens, collected mostly in Southeast Asia and the Palaearctic, as well as in the Afrotropics, Australia, and North and South America. Among them, we found type specimens of 509 taxa, described by Karawajew and other myrmecologists. The compiled Catalogue includes data on types of 80 taxa belonging to the subfamilies Dorylinae, Amblyoponinae, Ectatomminae, Ponerinae, Proceratiinae and Pseudomyrmecinae.